Análise da estratégia de marcha em crianças, adultos jovens e idosas através das forças de reação do solo - Lindemann, Vandressa Vargas Lindemann (2020)
Clinical gait analysis is essential to measure and interpret biomechanical parameters related to locomotion. The assessment during the life cycle is an important tool to understand the normal gait processes, to assist health professionals in diagnosing pathological processes resulting from aging and in choosing the most appropriate interventions to control age related changes. The aim of this study was to compare the ground reaction forces and its derived parameters – vertical and anteroposterior – during the walk, in different life phases. Participants were selected by intentional sampling, comprising three groups: children, young adults, and elderly women. The tests consisted of five repetitions of usual walking along a 6.0 m walkway containing 8 force platforms. The platforms captured ground reaction forces at 1000 Hz and data were recorded from both feet. The results were compiled into four original articles, presented in this study, and largely corroborate the findings of the literature regarding the maturation of gait during growth, and its limitations, due to aging. The main findings of the study confirm that some changes in gait, present in old age, happen more slowly and gradually throughout life, while others appear with the event of aging, as compensatory strategies to increase stability and improve balance.